Li-Hong Tang alleviates dextran sodium sulfate-induced colitis by regulating NRF2/HO-1 signaling pathway and gut microbiota - Gu, Hong; Tian, Yuwen; Xia, Jingjing; Deng, Xiaoyue; Chen, Jian; Jian, Tunyu; Ma, Jiong (Frontiers in Pharmacology, 2024)
Introduction: Ulcerative colitis (UC) is marked by recurring inflammation. Existing treatments are ineffective and may have toxic side effects. Thus, new therapeutic agents are urgently needed. We studied the botanical formula "Li-Hong Tang (LHT)", which contains two main ingredients, Salvia plebeia R. Br and Rhodiola crenulata (Hook. f. et Thoms.) H. Ohba. In this study, we aimed to identify the effects of LHT on UC and explore its potential mechanism. Methods: LHT was analyzed using a mass spectrometer (MS). DSS at a dose of 2.5% was utilized to develop UC in mice. The administered groups received low, medium, and high dosages (0.32 g/kg, 0.64 g/kg, and 1.28 g/kg) of LHT and the positive medication, sulfasalazine (0.2 g/kg), respectively. Body weight, disease activity index (DAI) score, colon length, spleen index, serum myeloperoxidase (MPO), nitric oxide (NO), superoxide dismutase (SOD) and inflammatory factor concentrations were monitored. The expression of NRF2 and HO-1 in colonic tissues was evaluated by immunohistochemistry. 16S rDNA sequencing was employed to investigate alterations in the gut microbiota of the mice, aiming to elucidate the extent of LHT's impact. Results: LHT may ameliorate DSS-induced colitis in mice by lowering inflammation, reducing oxidative stress, restoring the intestinal barrier, and influencing the NRF2/HO-1 pathway. Moreover, LHT treatment exhibited a regulatory effect on the gut microbiota, characterized by elevated levels of Patescibacteria, Verrucomicrobiota, Candidatus_Saccharimonas, Lactobacillus, and Ligilactobacillus levels while decreasing Oscillibacter and Colidextribacter levels. Further study indicated that MPO, NO, and inflammatory factors were positively correlated with Oscillibacter, Colidextribacter, Escherichia-Shigella, Anaerostines, and negatively with Lactobacillus, Clostridiales_unclassified, Candidatus_Saccharimonas, and Patescibacteria. Furthermore, colony network analysis revealed that Lactobacillus was negatively associated with Oscillibacter and Colidextribacter, whereas Oscillibacter was positively related to Colidextribacter. Conclusions: LHT protects against DSS-induced mice by inhibiting the inflammatory response, oxidative stress, and mucosal injury. The protective role may involve regulating the NRF2/HO-1 signaling pathway and gut microbiota.